M to T Rearrangement: An Approach to Correct Webbed Neck Deformity. (9th January 2014) - Murthy, Ananth S.; McGraw, Margeaux
Abstract : For the Noonan syndrome patient, the most concerning physical defect is often congenital webbing of the neck or pterygium colli. We present a patient with pterygium colli and a low and laterally displaced nuchal hairline. Since its description, various surgical approaches have been implemented to correct the deformity. Previously reported posterior and lateral approaches have notable disadvantages with regard to hairline displacement and recurrence. In order to address these disadvantages, a new surgical technique was used on this patient. We have termed this technique an M to T rearrangement. Using a lateral approach, the M and T incisions are made and the trapezial fascial web is directly visualized and able to be completely excised. This prevents the recurrence seen with the use of posterior techniques. Inferolateral displacement of hair-bearing skin can be removed with resection of the superior intervening triangle and improves the appearance of the low nuchal hairline. The excision of excess skin along with the zig-zag closure also prevents postoperative scar contraction and recurrence. An important effect of this technique is the prevention of anterior displacement of hair bearing skin. M to T rearrangement is an effective technique for the correction of webbed neck deformities seen in Noonan and Turner syndromes.